The Influence of Service Quality and Product Quality on Customer Retention with Customer Satisfaction as a Mediating Variable - Saputra, Gema Akbar Giri; Supriyadi, Didit; Setiawan, Rahyuniati (Golden Ratio of Mapping Idea and Literature Format, 2026)
The objective of this study is to examine the impact of service quality and product quality on customer retention, with customer satisfaction serving as a mediating variable, in the context of Basreng (fried meatball) products in PD Mekarsari Garut. A quantitative approach was employed, entailing the distribution of questionnaires to 384 respondents selected through non-probability sampling with the Purposive sampling method. The data analysis was conducted using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The findings of the study suggest a positive and significant relationship between service quality (X1) and product quality (X2) on customer satisfaction (Z). Furthermore, the study found that customer satisfaction (Z) significantly influences customer retention (Y). Furthermore, service quality (X1) and product quality (X2) exert a direct and indirect influence on customer retention (Y), with customer satisfaction (Z) functioning as a mediating factor. The R-square values of 0.625 for customer satisfaction (Z) and 0.425 for customer retention (Y) suggest that the model possesses adequate predictive capability. These findings underscore the significance of maintaining and enhancing service quality (X1) and product quality (X2) to foster customer satisfaction (Z) and cultivate long-term retention. The practical implications of this study suggest that businesses, particularly Basreng PD Mekarsari, should prioritize enhancing their service and product quality as a strategy to maintain customer retention in a competitive market.